A tale of two conditions: when people living with HIV meet three doses of inactivated COVID-19 vaccines - Tan, Yuting; Zou, Shi; Ming, Fangzhao; Wu, Songjie; Guo, Wei; Wu, Mengmeng; Tang, Weiming; Liang, Ke (Frontiers in Immunology, 2023)
Background Currently, data on long-term immune responses to a homogenous booster dose of the inactivated COVID-19 vaccine are still limited among people living with HIV (PLWH). Methods A prospective cohort study with a 13-month follow-up was conducted in China between March 2021 and August 2022 to evaluate the dynamics of SARS-CoV-2 specific humoral and cellular immunity against three doses of the inactivated COVID-19 vaccine from before the first dose until 6 months after the booster dose vaccination among PLWH in comparison to healthy controls (HC). Results 43 PLWH on antiretroviral therapy (ART) and 23 HC were enrolled. Compared with HC, the neutralizing antibodies (nAbs) levels among PLWH were significantly lower on days 14, 30, 60, 90, and 120 after the booster dose vaccination. Among PLWH, the nAbs titers on days 14, 30, and 60 after the booster dose were significantly higher than the peak of the second dose. However, on day 180 after the booster dose, the nAbs titers were similar to the peak of the second dose vaccination. Compared with HC, the frequencies of IFN-γ-secreting and TNF-α-secreting CD4+ and CD8+ T cells among PLWH were lower on days 14 and 180 after the booster dose vaccination. Among PLWH, increased T cell immunity was induced by the booster dose of the vaccine and kept stable on day 180 after the booster dose vaccination. Conclusion Although a homogenous booster dose following two doses of the inactivated COVID-19 vaccine among PLWH could elicit higher nAb titers, reduce antibody decay, and maintain T cell responses even 6 months after vaccination, the overall immunogenicity of the booster dose was found to be lower among PLWH than among healthy controls. Further strategies are needed to improve immunogenicity to the inactivated COVID-19 vaccine among PLWH.